The transport limited currents at insonated electrodes - Banks, C; Compton, R; Fisher, A; Henley, L (2004)
We investigate the transport limited currents (ILim) observed at electrodes placed 'face-on' to a sonic transducer such that a significant convective flux arising from acoustic streaming is observed. Experiments conducted at 25 kHz with turbulent solution flow concerned with the oxidations of iodide or ferrocyanide and the reductions of ruthenium hexammine(III) or the hydrogen ion, all in aqueous solution, over a wide range of conditions, including those of variable kinematic viscosity (v) controlled by the addition of sucrose to the electrolyte solution and changing ultrasound power (Pw) are used to show that the following equation accurately predicts the observed limiting currents, ILim = C(h,v)D2/3AC bulkPw1/2 where A is the electrode area, C bulk is the concentration of the redox active species, D is the diffusion coefficient, and C is a function of v and of the electrode-to-horn separation, h which falls off strongly as h increases.